Analisis Sejarah Penyebab Awal Konflik antara Amerika Serikat dan Iran - Purba, Jesika Indah Sari; Harifin, Harifin; Simamora, Shintya; Nazwa, M. Dirham; Br Perangin-angin, Desta Riani; br Sembiring, Santa Hoky (Polyscopia, 2024)
The conflict between the United States and Iran is one of the most prominent and complex geopolitical issues in the world. This research aims to analyze the initial causes of the conflict between the two countries from a historical perspective. It begins in the early 20th century with the increasing Western interest in Iranian oil and covers the fall of Prime Minister Mohammad Mossadegh in 1953 through a CIA-backed coup, which was a pivotal moment affecting bilateral relations. The study also examines the 1979 Iranian Revolution, which ended the US-backed Shah's regime and marked the start of open hostility. Using historical research methods and document analysis, the study identifies economic, political, and ideological factors that contributed to the escalation of the conflict. The findings show that a combination of foreign intervention, economic interests, and domestic political changes in Iran have played a crucial role in shaping the hostility between the United States and Iran. These insights provide a deeper understanding of the root causes underlying the ongoing conflict.